2012
DOI: 10.1292/jvms.11-0577
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Feline Coronavirus Antibodies in Japanese Domestic Cats during the Past Decade

Abstract: AbSTRACT. From 2001From to 2010 Japanese cats were examined for feline coronavirus (FCoV) antibodies. The seroprevalence of purebreds (66.7%) was higher than that of random breds (31.2%). Seroprevalence increased greatly in purebreds by three months of age, while it did not fluctuate greatly in random breds with aging, indicating that cattery environments can contribute to FCoV epidemics. Purebreds from northern regions of Japan were likely to be seropositive (76.6% in Hokkaido, 80.0% in Tohoku), indicating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 11 publications
6
19
0
1
Order By: Relevance
“…In our study, the prevalence of FCoV was not significantly associated with sex, which is in agreement with several studies (Bell et al., ; Sharif et al., ; Taharaguchi, Soma, & Hara, ). On the contrary, several studies have shown that FCoV infection appeared to be significantly correlated with the male sex (Pesteanu‐Somogyi, Radzai, & Pressler, ; Worthing et al., ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In our study, the prevalence of FCoV was not significantly associated with sex, which is in agreement with several studies (Bell et al., ; Sharif et al., ; Taharaguchi, Soma, & Hara, ). On the contrary, several studies have shown that FCoV infection appeared to be significantly correlated with the male sex (Pesteanu‐Somogyi, Radzai, & Pressler, ; Worthing et al., ).…”
Section: Discussionsupporting
confidence: 94%
“…In our study, FCoV infection was significantly associated with young cats (aged <6 months). Other studies have reported that cats of ages ranging from 3 to 11 months exhibit a higher FCoV prevalence than those of other ages (Bell et al., ; Pedersen, ; Taharaguchi et al., ). However, FCoV infection in Australia and Malaysia was reported not to be associated with age (Bell et al., ; Sharif et al., ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This study shows that FCoV infections are widespread in cats from Istanbul and this is in agreement with other studies elsewhere (Sparkes et al, 1992;Pedersen et al, 2004;Pesteanu-Somogyi et al, 2006;Sharif et al, 2009;Taharaguchi et al, 2012;Paris et al, 2014). Moreover, FCoV seroprevalence increased in 2014 compared to previous years and this may suggest that FCoV infections are an increasing health problem in cats in Istanbul.…”
Section: Discussionsupporting
confidence: 92%
“…Worldwide the prevalence of FCoV infections may be up to 90% in multi-cat environments and 10-60% in household cats (Herrewegh et al, 1997;Pedersen et al, 2004;Bell et al, 2006;Addie et al, 2009;Sharif et al, 2009;Taharaguchi et al, 2012). Detection of FCoV antibodies in the early stage of infection can be useful to minimize the spread of FCoVs in a breeding cattery, multi-cat household and FCoV-free household (Cave et al, 2004;Dye et al, 2008;Drechsler et al, 2011).…”
Section: Introductionmentioning
confidence: 99%